Enhancing soil nutrients for yield and nutritional quality of carrot through the joint effect of a complementary technology package in the rainforest region of Nigeria (International Journal of Agricultural Research, Innovation and Technology, 2025)
Field experiments were conducted to assess the effects of integrated application of poultry manure (PM), cocoa pod husk (CPH), and NPK 15:15:15 fertilizer on carrot root yield and nutritional quality during 2023 and 2024 cropping seasons at Adeyemi Federal University of Education (07°04'N, 04°49'E), Ondo in the rainforest ecology of southwest Nigeria. Poultry waste and CPH were combined at three different quantities (0, 5, 10 t ha-1), with NPK fertilizer applied at three levels (0, 100, 200 kg ha-1) in a factorial experiment set up in a randomized complete block layout. Each treatment was repeated three times. The gathered data were assessed using the Statistical Analysis System Institute Package. The site's soil had low levels of accessible P (4.87 mg kg-1), nitrogen (0.7 g kg-1), and a somewhat acidic pH (6.1). Plots with the combined application of the three soil amendments showed a significant (P